The impact of computers on Certified Public Accountants in Singapore - School of Accountancy and Business (2008)
A questionaire survey among the members of the Institute of Certified Public Accountants of Singapore was conducted to determine how much the accountants are dependent on computers for their work, the impacts of computers on their jobs, the information systems skills and knowledge useful to their jobs and their opinions on the impact of IT on the accounting profession.